Penggunaan Media Pembelajaran Aurora 3D Presentation untuk Meningkatkan Minat dan Hasil Belajar Siswa dalam Mata Pelajaran Sejarah - Endang Wahyuni (Universitas Tadulako, 2021)
This study aimed to determine the increase in student interest and learning outcomes through the use of Aurora 3D Presentation learning media in grade 10th of TMP B SMKN 3 Palu, 2018/2019 Academic Year. This research was a classroom action research. Each cycle consisted of planning, implementing the action, observing (observing) and reflecting. The subjects of this study were all students of class 10th TMP B, with the total of 36 students. Data collection techniques included observation and tests. The data were analysed used a qualitative descriptive analysis. The results showed that the use of Aurora 3D Presentation learning media can increase interest and learning outcomes of grade 10th TMP B SMKN 3 Palu in the 2018/2019 academic year. The increase in student interest in learning in the first cycle with an average score of 2.8 in the medium category then increased in the second cycle with an average score of 3.4 in the high category. The increase in student learning outcomes can also be seen from the average value and the percentage of classical completeness. In the first cycle, the students' average score was 75.43 with 62.5% completeness. However, it increased in cycle II with an average value of 84.3 with a percentage of classical completeness of 86.78%.